(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the outcomes of obese patients with multi vessel coronary artery disease undergoing Off Pump coronary artery bypass graft (CABG) surgery. Study Design: A retrospective study Place and Duration of Study: This study was conducted at the Cardiac Surgery department of Choudhary Pervaiz Elahi Institute of Cardiology (CPEIC) Multan from January 2021 to August 2021 for a period of 08 months. Materials and Methods: All the patients that underwent OPCAB were grouped in two categories on basis of BMI, In A group patients were obese and in B group patients were non-obese. They were compared for the following variables: age, gender, weight, Heart association of New York Functional Class (NYHA), Angina Class of Canadian Cardiovascular Society (CCS), extent of coronary artery involved disease, Number of grafts and left ventricular ejection fraction (EF). Data in groups was compared by using ANOVA test in normally distributed variables and in not normally distributed variables Kruskal-Wallis test was applied. P-value of less than 0.05 was taken as significant. Results: Majority of patients in our study were males. (87%, n=75) whereas only 11 % (n=9) patients were female. The mean age of patients in our study was 43.36±7.6 years. The most important finding of this study is that the rate morbidity and mortality was same in the patients that were labelled as obese and non-obese and underwent OPCAB. Regarding the post-operative course mean duration of inotrope usage was 11.17±2.29 hours and when the comparison was done among the two study groups a statistically significant was observed (p<0.05). Conclusion: In obese patients off pump coronary artery bypass grafting is beneficial. These patients are already compromised due to the associated side effects of obesity and avoiding CPB may be beneficial for short term outcome of these patients.